Bovine respiratory disease in beef calves supported long transport stress: An epidemiological study and strategies for control and prevention. (March 2021) - Pratelli, Annamaria; Cirone, Francesco; Capozza, Paolo; Trotta, Adriana; Corrente, Marialaura; Balestrieri, Anna; Buonavoglia, Canio
Abstract: BRD is associated with infectious agents, but management and transport-stress are trigger factors. Metaphylactic administration of antimicrobial reduces colonization of respiratory tract by pathogens, but the development of antibiotic-resistance raises public health concerns leading to propose new control strategies. The study analyzed nasopharyngeal swabs of 231 imported cattle, 10% of 49 trucks, transported from France to southern Italy and, through Real-time PCR identified the prevalence of the involved pathogens speculating on strategies to reduce the impact of BRD. The samples were tested by Real-time PCR, for the detection of bovine coronavirus (BCoV), bovine respiratory syncytial virus (BRSV), bovine parainfluenza virus (BPiV), bovine adenovirus (BAdV), Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, and Mycoplasma bovis . Yates-corrected chi squared, or Fisher's exact test were used to compare both animal-health status and positivity/negativity to pathogens, and the relationship between presence/absence of clinical signs and Real-time PCR-positivity. H. somni and BCoV were the most frequently identified pathogens. In BRD-diagnosed cattle, BAdV was detected in 13.8% (19/138), BRSV in 14.5% (20/138) and BPiV in 4.3% (6/138). Healthy cattle were mostly positive for H. somni (89.2%, 83/93). A statistically significant association was observed between clinical signs and positivity to M. haemolytica ( p value = 0.016). Although mass-medication and vaccination are used for BRD control, it still remains a primary health problem. Our results highlight that the nasopharyngeal microbiota could be affected by transport and that strategies to enhance calf immunity for reducing BRD-risk development would be more effective if applied at farm of origin prior to loading. Highlights: Bovine Respiratory Disease (BRD) is the most common and costly disease in feedlot cattle. Nasopharyngeal microflora undergoes changes after transport in sick/healthy animals providing insights regarding the pathogenesis and the improving management practices. Laboratory tests on the nasopharyngeal swabs of cattle can identify the prevalent BRD-pathogens. A statistically significant association was observed between clinical signs and positivity to M. haemolytica (p value = 0.016). Good management practices to enhance immunity prior to loading should be applied to reduce the risk of BRD and/or the incidence of the disease.